2015
DOI: 10.1523/jneurosci.2999-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Recency, Repetition, and the Multidimensional Basis of Recognition Memory

Abstract: Recency and repetition are two factors that have large effects on human memory performance. One way of viewing the beneficial impact of these variables on recognition memory is to assume that both factors modulate a unidimensional memory trace strength. Although previous functional neuroimaging studies have indicated that recency and repetition may modulate similar brain structures, particularly in the region of the inferior parietal cortex, there is extensive behavioral evidence that human subjects can make i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The reduction in training advantage for real-world practice from immediate to delayed retention may stem from the increase in the number of repetitions performed during the tablet-based simulations following the attainment of a performance plateau. Practice repetitions following knowledge acquisition is well evidenced to strengthen learning of both semantic information [ 58 , 59 ] and motor tasks [ 60 62 ], as well as simultaneous, but separate, cognitive and motor procedures [ 63 ]. Accordingly, the development of many digital learning platforms have relied nearly entirely on manipulating spaced-timing repetitions of the presented information [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in training advantage for real-world practice from immediate to delayed retention may stem from the increase in the number of repetitions performed during the tablet-based simulations following the attainment of a performance plateau. Practice repetitions following knowledge acquisition is well evidenced to strengthen learning of both semantic information [ 58 , 59 ] and motor tasks [ 60 62 ], as well as simultaneous, but separate, cognitive and motor procedures [ 63 ]. Accordingly, the development of many digital learning platforms have relied nearly entirely on manipulating spaced-timing repetitions of the presented information [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results show a weak acquisition of recognition memory across the perceptual task, in agreement with studies of that compared recognition memory of perceptual experts – such as cytologists, radiologists – and naive participants which showed that experts are slightly better than non-experts at remembering images of the expertise category, but this memory is substantially inferior compared to the one for everyday scenes and objects ( Evans et al, 2011 ), suggesting that perceptual discrimination and identification tasks do not necessarily promote the acquisition of a recognition memory. In contrast, memory studies have shown that experts have superior recognition memory for the expertise category ( Nyhus and Curran, 2009 ; Herzmann and Curran, 2011 ), but these studies were conducted with stimuli categories that include semantic representations, which enhance deep coding leading to superior familiarity and recall ( Buchsbaum et al, 2015 ). Thus, the practice of a perceptual task does not necessarily foster the acquisition of a recognition memory unlike what happens in a memory task.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in training advantage for real-world practice from immediate to delayed retention may stem from the increase in the number of repetitions performed during the tablet-based simulations following the attainment of a performance plateau. Practice repetitions following knowledge acquisition is well evidenced to strengthen learning of both semantic information [58,59] and motor tasks [60][61][62], as well as simultaneous, but separate, cognitive and motor procedures [63]. Accordingly, the development of many digital learning platforms have relied nearly entirely on manipulating spacedtiming repetitions of the presented information [64].…”
Section: Procedural Efficiency Across Training Protocolsmentioning
confidence: 99%